Relevansi Pendidikan Islam dalam Membangun Karakter Generasi Milenial - Khoiroh, Nabilatul (Maliki Interdisciplinary Journal, 2025)
This abstract explores the urgency of Islamic education in building the character of millennial generation in the digital era. Millennial generation, raised in an era of technological advancement, face unique challenges and opportunities in shaping their identity. Islamic education plays a crucial role in equipping this generation with strong values, morals, and spirituality, serving as a solid foundation in facing the dynamics of the times. This article outlines key aspects of Islamic education that are relevant to the formation of millennial character, such as noble character, social responsibility, and emotional intelligence. Noble character, encompassing honesty, courtesy, and compassion, becomes an important moral foundation in interacting with the digital world. Social responsibility encourages millennials to play an active role in advancing society, both in the real world and in cyberspace. Emotional intelligence, which includes the ability to manage emotions and build empathy, helps millennials cope with pressures and challenges in the digital age. Through comprehensive Islamic education, millennials can find a balance between technological advancement and noble values, enabling them to face challenges and utilize opportunities in the digital era wisely.